Obstetric ultrasound aids prompt referral of gestational trophoblastic disease in marginalized populations on the Thailand-Myanmar border - Kathryn McGregor; Aung Myat Min; Noaeni Karunkonkowit; Suporn Keereechareon; Mary Ellen Tyrosvoutis; Nay Win Tun; Marcus J. Rijken; Gabie Hoogenboom; Machteld Boel; Kesinee Chotivanich; François Nosten; Rose McGready (Taylor & Francis Group, 2017)
Background: The use of obstetric ultrasound in the diagnosis of gestational trophoblastic disease (GTD) in high-income settings is well established, leading to prompt management and high survival rates. Evidence from low-income settings suggests ultrasound is essential in identifying complicated pregnancies, but with limited studies reviewing specific conditions including GTD. Objective: The aim of this study is to review the role of ultrasound in diagnosis and management of GTD in a marginalized population on the Thailand-Myanmar border. Antenatal ultrasound became available in this rural setting in 2001 and care for women with GTD has been provided by Thailand public hospitals for 20 years. Design: Retrospective record review. Results: The incidence of GTD was 103 of 57,004 pregnancies in Karen and Burmese women on the Thailand-Myanmar border from 1993-2013. This equates to a rate of 1.8 (95% CI 1.5-2.2) per 1000 or 1 in 553 pregnancies. Of the 102 women with known outcomes, one (1.0%) died of haemorrhage at home. The median number of days between first antenatal clinic attendance and referral to hospital was reduced from 20 (IQR 5-35; range 1-155) to 2 (IQR 2-6; range 1-179) days (p = 0.002) after the introduction of ultrasound. The proportion of severe outcomes (death and total abdominal hysterectomy) was 25% (3/12) before ultrasound compared to 8.9% (8/90) with ultrasound (p = 0.119). A recurrence rate of 2.5% (2/80) was observed in the assessable population. The presence of malaria parasites in maternal blood was not associated with GTD. Conclusions: The rate of GTD in pregnancy in this population is comparable to rates previously reported within South-East Asia. Referral time for uterine evacuation was significantly shorter for those women who had an ultrasound. Ultrasound is an effective method to improve diagnosis of GTD in low-income settings and an effort to increase availability in marginalized populations is required.